STRATEGI PEMASARAN SEMEN MERAH PUTIH UNTUK MENINGKATKAN KEPUASANA PELANGGAN PADA CV. ADI CANDRA SUMEKAR KABUPATEN SUMENEP - Moh. Kurdi (Journal of Social Sustainability Management, 2022)
In facing competition in the business sector, the company must be able to determine the level of customer satisfaction. Marketing in monitoring customer satisfaction (consumers) has seen customer complaints with satisfaction status influenced by consumer complaints. Consumer complaints have been used as a benchmark to determine service satisfaction from the company in distributing red and white cement to customers. This research is a qualitative descriptive study with the process of collecting data on primary data and secondary data. The method of analysis used in this research is SWOT analysis. From the research results it can be concluded that the marketing carried out by CV. Adi Chandra Sumekar is in quadrant III, which means that he must optimize his strength to minimize the threat that exists.